The GaN trench gate MOSFET with floating islands: High breakdown voltage and improved BFOM. (February 2018) - Shen, Lingyan; Müller, Stephan; Cheng, Xinhong; Zhang, Dongliang; Zheng, Li; Xu, Dawei; Yu, Yuehui; Meissner, Elke; Erlbacher, Tobias
Abstract: A novel GaN trench gate (TG) MOSFET with P-type floating islands (FLI) in drift region, which can suppress the electric field peak at bottom of gate trench during the blocking state and prevent premature breakdown in gate oxide, is proposed and investigated by TCAD simulations. The influence of thickness, position, doping concentration and length of the FLI on breakdown voltage (BV) and specific on-resistance (Ron_sp ) is studied, providing useful guidelines for design of this new type of device. Using optimized parameters for the FLI, GaN FLI TG-MOSFET obtains a BV as high as 2464 V with a Ron_sp of 3.0 mΩ cm 2 . Compared to the conventional GaN TG-MOSFET with the same structure parameters, the Baliga figure of merit (BFOM) is enhanced by 150%, getting closer to theoretical limit for GaN devices. Highlights: This paper proposes a novel GaN trench gate (TG) MOSFET with P-type floating islands (FLI) in the drift region and investigates it by TCAD simulations. It is found that P-type FLI can suppress electric field peak at bottom of gate trench during blocking state and prevent premature breakdown in gate oxide. Using optimized parameters, GaN FLI TG-MOSFET reaches a breakdown voltage (BV) as high as 2464 V with a specific on-resistance (Ron_sp ) of 3.0 mΩ cm 2, achieving 150% higher Baliga figure of merit (BFOM) than GaN TG-MOSFET reported by TOYODA GOSEI. The influence of thickness, position, doping concentration and length of the FLI on BV and Ron_sp is studied, which provides useful guidelines for the design of this new type of device.